Re-building the Nation-State: The American Civil War in a transnational perspective - Daniele Fiorentino (Amnis)
This article analyzes the reading of the American Civil War in Europe, how this conflict was perceived. It shows the international dimension of this war and insists on the idea that it fed the reflection on the European fights.